Determinants of the Uptake of NHIF Medical Cover by Informal Sector Workers: A Case of UNAITASSACCO Members in Murang'a County - Kituku, Anastasia M.; Amata, Evans (Journal of Public Policy and Administration, 2016)
Purpose: The purpose of this study was to establish the major determinants of uptake of medical cover at Kenya's National Health Insurance Fund by informal sector workers among UNAITAS SACCO members in Murang'a County. Methodology: The study adopted a descriptive survey design. The target population comprised of all members of UNAITAS SACCO in Murang'a County. The population was 68,000 members who were in existence as at December 2014 (SASRA, 2014). Stratified random sampling technique was used to select 150members in the informal sector participating in the study. A likert scale questionnaires was used to collect quantitative data. Statistical package for social science (SPSS) was used to draw inferences from the coded data. Results: Results revealed that the major determinants of level of uptake of medical cover at Kenya's National Health Insurance Fund by informal sector workers among UNAITAS SACCO members in Murang'a County were namely income level, awareness of NHIF benefits, access to NHIF outlet and the amount of premiums payable. The results also revealed that there were other determinants of uptake of NHIF medical scheme. These included gender of the head of the household, the level of education, presence of children, age and marital status. Unique contribution to theory, practice and policy: The study recommended that the government should educate the people operating within the informal sector on better ways of accessing finance so as to increase their capital and as result increase their levels of income. This would result to increased uptake of the NHIF medical scheme.